PENERAPAN VIDEO DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI TAKENGON - Nidawati Nidawati (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2019)
Madrasah Tsnawiyah Negeri (MTsN) is a First Level School (SMP) which is characterized by Islam. The Madrasah curriculum is entirely the same as the school in general coupled with Islamic religious characteristics. In learning English students are given the same material, use the same teaching materials, the same way of learning, get the same treatment from the teacher and are expected to get learning outcomes that are all good. Just as is known, each individual has different characteristics. Likewise with students, as individuals, students with one another have differences. Differences between these individuals can later influence how the learning process will take place and the achievement of learning objectives. This study aims to determine the application of video media in improving student achievement in English lessons at Takengon. The method used in this method is the experimental method. Data collection research was conducted using tests and questionnaires. The results of this study indicate that the application of video in improving student learning achievement at the English Language Study in Takengon with the acquisition of average scores of students 75 and 86.